L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Menstruation: Science and society - Critchley, Hilary O. D.; Babayev, Elnur; Bulun, Serdar E.; Clark, Sandy; Garcia-Grau, Iolanda; Gregersen, Peter K.; Kilcoyne, Aoife; Kim, Ji-Yong Julie; Lavender, Missy; Marsh, Erica E.; Matteson, Kristen A.; Maybin, Jacqueline A.; et al. (American Journal of Obstetrics and Gynecology, 2020)
Women's health concerns are generally underrepresented in basic and translational research, but reproductive health in particular has been hampered by a lack of understanding of basic uterine and menstrual physiology. Menstrual health is an integral part of overall health because between menarche and menopause, most women menstruate. Yet for tens of millions of women around the world, menstruation regularly and often catastrophically disrupts their physical, mental, and social well-being. Enhancing our understanding of the underlying phenomena involved in menstruation, abnormal uterine bleeding, and other menstruation-related disorders will move us closer to the goal of personalized care. Furthermore, a deeper mechanistic understanding of menstruation-a fast, scarless healing process in healthy individuals-will likely yield insights into a myriad of other diseases involving regulation of vascular function locally and systemically. We also recognize that many women now delay pregnancy and that there is an increasing desire for fertility and uterine preservation. In September 2018, the Gynecologic Health and Disease Branch of the Eunice Kennedy Shriver National Institute of Child Health and Human Development convened a 2-day meeting, "Menstruation: Science and Society" with an aim to "identify gaps and opportunities in menstruation science and to raise awareness of the need for more research in this field." Experts in fields ranging from the evolutionary role of menstruation to basic endometrial biology (including omic analysis of the endometrium, stem cells and tissue engineering of the endometrium, endometrial microbiome, and abnormal uterine bleeding and fibroids) and translational medicine (imaging and sampling modalities, patient-focused analysis of menstrual disorders including abnormal uterine bleeding, smart technologies or applications and mobile health platforms) to societal challenges in health literacy and dissemination frameworks across different economic and cultural landscapes shared current state-of-the-art and future vision, incorporating the patient voice at the launch of the meeting. Here, we provide an enhanced meeting report with extensive up-to-date (as of submission) context, capturing the spectrum from how the basic processes of menstruation commence in response to progesterone withdrawal, through the role of tissue-resident and circulating stem and progenitor cells in monthly regeneration-and current gaps in knowledge on how dysregulation leads to abnormal uterine bleeding and other menstruation-related disorders such as adenomyosis, endometriosis, and fibroids-to the clinical challenges in diagnostics, treatment, and patient and societal education. We conclude with an overview of how the global agenda concerning menstruation, and specifically menstrual health and hygiene, are gaining momentum, ranging from increasing investment in addressing menstruation-related barriers facing girls in schools in low- to middle-income countries to the more recent "menstrual equity" and "period poverty" movements spreading across high-income countries.
Number: 5
Keywords: amériques; corps; discipline; endométriose; gynécologie; menstruations; médecine; projet charge mentale; régions géographiques; santé; santé des femmes*; santé menstruelle; sciences; thématiques; états-unis